SNOW PARTICLE SIZE DISTRIBUTIONS AT SYOWA STATION, ANTARCTICA IN 1988 - ハタナカ, マサヒコ; キムラ, シンヤ; ヨシダ, ユタカ; ワダ, マコト; ヒラサワ, ナオヒコ; HATANAKA, Masahiko; KIMURA, Shinya; YOSHIDA, Yutaka; WADA, Makoto; HIRASAWA, Naohiko (National Institute of Polar Research, 1999)
P(論文) For meteorological radar observations, it is very important to know the size and the characteristics of precipitation particles. In this paper, we report the snow particle size distributions at Syowa Station, Antarctica in 1988 using snow particle VCR tapes, which were recorded by a specially designed portable video camera set on the ground. The digitized video images retrieved from the VCR tape are processed to separate each snow particle on the image. We measured the three kinds of snow particle "radius" on the separated snow particle image and obtained the snow particle size distributions. Using the five sets of VCR tapes, we obtained four cases of distributions at Syowa Station in 1988 and estimated a case of snowfall rate from the distribution. departmental bulletin paper